1998
DOI: 10.1074/jbc.273.48.31691
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Isoleucyl-tRNA Synthetase from Staphylococcus aureus

Abstract: The interactions of isoleucyl-tRNA synthetase (IleRS,E

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 31 publications
4
41
0
Order By: Relevance
“…5, using Grafit (version 5) for each inactivator concentration. This regression simultaneously estimates the apparent rate constant for the formation of the final steady state equilibrium (K obs ) plus the initial and steady state velocities of product formation (V 0 and V s ) for each curve analyzed (Morrison and Walsh, 1988;Pope et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5, using Grafit (version 5) for each inactivator concentration. This regression simultaneously estimates the apparent rate constant for the formation of the final steady state equilibrium (K obs ) plus the initial and steady state velocities of product formation (V 0 and V s ) for each curve analyzed (Morrison and Walsh, 1988;Pope et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…Progress curve analysis uses an "all-in" approach where the enzyme is exposed simultaneously to probe substrate and inactivator/inhibitor while enzyme activity is monitored throughout the inactivation. This type of analysis has long been an accepted tool for measuring presteady state kinetics for a variety of physiological enzymes (Orson and Tipton, 1979;Pope et al, 1998;Maurer et al, 2000;Dash et al, 2001). However, its use in the context of P450 inactivation is unprecedented.…”
mentioning
confidence: 99%
“…Pseudomonic acid has been hypothesized to be an analogue of IleRS small substrates or intermediate isoleucyl-AMP (2,4,23,25). The mode of action of pseudomonic acid has been compared in detail with those of isoleucyl-AMP analogues (49). Recent crystallographic analysis of T. thermophilus IleRS complexed with the isoleucyl-AMP analogue suggested that the antibiotic blocks the binding of active intermediate isoleucyl-AMP (24).…”
Section: Fig 6 P Fluorescensmentioning
confidence: 99%
“…For example, the antibiotic mupirocin 3 ( Figure 6) exerts its action by selectively inhibiting prokaryotic isoleucyl-tRNA synthetases (145,146), and phosmidosine 4 ( Figure 6) (147, 148) likely inhibits prolyltRNA synthetase by effectively mimicking the acyladenylate intermediate formed by this enzyme. These findings therefore resulted in the development of efficient synthetic routes for preparing chemically stable analogs of acyladenylates (148)(149)(150) in the expectation that such compounds will exhibit antibacterial activity coupled with low mammalian toxicity (151,152). In light of these studies (145)(146)(147)(148)(149)(150), β-asparaginyladenylate 5 ( Figure 6) was synthesized (153) The relatively lengthy synthetic route to obtain this compound and the presence of a charged phosphoamidate functional group argue against its likely clinical utility.…”
Section: Sulfonamide Derivatives As Inhibitors Of Human Asparagine Symentioning
confidence: 99%